Health Protocol of Covid-19: as A Prevention of Covid-19 in the Work Area of Office Employees in Bandar Lampung - Nova Nurwinda Sari; Dewi Yuliana; Radella Hervidea; Annisa Agata (Global Health Science Group, 2020)
Coronavirus disease 2019 (Covid-19) is a disease caused by the corona virus which can cause respiratory tract infections with up to severe symptoms. SARS-CoV-2 virus infection can cause symptoms ranging from symptoms (asymptomatic), mild, moderate and severe symptoms. Until now, no antiviral or vaccine has been found that can infect Covid-19. Therefore, efforts to break the chain of transmission are the application of health protocols that include 3M recording, wearing masks and maintaining distance. However, there are still many community members, especially employees who are not yet obedient to implementing this protocol. Community service is carried out as an effort to prevent the transmission of Covid-19 to office employees in Bandar Lampung, considering that the work area is one of the areas that contributes to the high incidence of Covid-19 in Bandar Lampung. The community service activity was attended by 97 well-known employees in 13 offices in the Bandar Lampung area. The method used is health education through the zoom application. The questionnaire was given to measure participants before and after participating in activities. The material is presented using powerpoint audiovisual media and leaflets which are presented using the zoom application. This activity results showed an increase in participants' knowledge about covid-19 and covid-19 health protocols in the work area. Presenting information about covid-19 and covid-19 health protocols has a positive impact on increasing public knowledge, especially employees in office areas.